Hydrolysis of proteins from Liza subviridis - Yu, S. Y.; R., Ahmad (Asian Fisheries Society, 1998)
Proteins from Liza suboiridis, a marine fish, were hydrolyzed using Alcalase 2.5L. The parameters studied were pH, temperature, ratio of enzyme to substrate concentration, and substrate concentration. It was observed that the optimum conditions for the hydrolysis were pH 9 at 40°C, using an enzyme to substrate ratio of 16 Au/kg and a substrate concentration of 5%.